Prenatal alcohol exposure dysregulates spinal and circulating immune cell circular RNA expression in adult female rats with chronic sciatic neuropathy - Noor, Shahani; Pritha, Ariana N.; Pasmay, Andrea A.; Sanchez, Jacob E.; Sanchez, Joshua J.; Fernandez-Oropeza, Annette K.; Sun, Melody S.; Dell’Orco, Michela; Davies, Suzy; Savage, Daniel D.; Mellios, Nikolaos; Milligan, Erin D. (Frontiers in Neuroscience, 2023)
Alcohol consumption during pregnancy is associated with Fetal Alcohol Spectrum Disorders (FASD) that results in a continuum of central nervous system (CNS) deficits. Emerging evidence from both preclinical and clinical studies indicate that the biological vulnerability to chronic CNS disease in FASD populations is driven by aberrant neuroimmune actions. Our prior studies suggest that, following minor nerve injury, prenatal alcohol exposure (PAE) is a risk factor for developing adult-onset chronic pathological touch sensitivity or allodynia. Allodynia in PAE rats occurs concurrently with heightened proinflammatory peripheral and spinal glial-immune activation. However, minor nerve-injured control rats remain non-allodynic, and corresponding proinflammatory factors are unaltered. A comprehensive molecular understanding of the mechanism(s) that underlie PAE-induced proinflammatory bias during adulthood remains elusive. Non-coding circular RNAs (circRNAs) are emerging as novel modulators of gene expression. Here, we hypothesized that PAE induces dysregulation of circRNAs that are linked to immune function under basal and nerve-injured conditions during adulthood. Utilizing a microarray platform, we carried out the first systematic profiling of circRNAs in adult PAE rats, prior to and after minor nerve injury. The results demonstrate a unique circRNA profile in adult PAE rats without injury; 18 circRNAs in blood and 32 spinal circRNAs were differentially regulated. Following minor nerve injury, more than 100 differentially regulated spinal circRNAs were observed in allodynic PAE rats. Bioinformatic analysis identified that the parental genes of these circRNAs are linked to the NF-κB complex, a central transcription factor for pain-relevant proinflammatory cytokines. Quantitative real-time PCR was employed to measure levels of selected circRNAs and linear mRNA isoforms. We have validated that circVopp1 was significantly downregulated in blood leukocytes in PAE rats, concurrent with downregulation of Vopp1 mRNA levels. Spinal circVopp1 levels were upregulated in PAE rats, regardless of nerve injury. Additionally, PAE downregulated levels of circItch and circRps6ka3, which are linked to immune regulation. These results demonstrate that PAE exerts long-lasting dysregulation of circRNA expression in blood leukocytes and the spinal cord. Moreover, the spinal circRNA expression profile following peripheral nerve injury is differentially modulated by PAE, potentially contributing to PAE-induced neuroimmune dysregulation.